Naturalness of Properties and Simplicity of Theories - Drobňák, Matej (Teorie vědy / Theory of Science, 2019)
In this paper, I discuss a specific approach to measuring and comparing the simplicity of theories that is based on Lewis’s notion of fundamental properties. In particular, I discuss the criterion of simplicity as stated by Williams. According to Williams, the best candidate for a theory is the one which has the shortest definition in terms of fundamental properties. The aim of this paper is to show that the criterion thus specified has two constraints. First, the criterion is not applicable to cases in which candidates for theories that specify fundamental properties are compared. Secondly, the applicability of the criterion in social sciences seems to be unwarranted.